INFORMATION SYSTEM FLOW DESIGN LIBRARY WEBSITE BASED SMKN 8 BANDUNG “THE ULTIMATE DIGITAL LIBRARY” - Muhammad Fiqh Nurhidayat; Ari Purno Wahyu Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Digital Library Smkn 8 Bandung has constraint in data management and efficiency service borrow and return the book made by the officer library. Data Collection library, visitor data, and transactions loan need needs will use technology webbased system information for simplify the process of performance in the Library of SMKN 8 Bandung. Study this aim build system information library web -based that will could help library data management and improve quality service to transaction borrowing from the library. Method used in development system information on research this is which waterfall method at which stage this there is design and implementation apply pattern model view controller (MVC) design. While the testing process carried out there is a number of Step testing by sequentially namely unit tests, integration tests, validation tests, reliability tests, compatibility tests, and acceptance tests. Unit tests using base path technique show results from system that has simple structure, very easy understood and implemented. Integration test using white box method shows valid results. Validation testing using black box method shows that 25 function walk with good. Reliability test with use nelson calculations show that system could walk with consistent. Compatibility test shows system could used with good on 4 types of browsers. And the acceptance test shows that all function succeed run with good and have accepted by SMKN 8 Bandung.